The modern model of the Arabian mass media: experience of the theoretically substantiate - Al-Boslani, Maged (Journal of the Belarusian State University. Journalism, 2019)
The globalization of the information space has brought about radical and lasting changes in the socio-political life of  Arab society, the economy, politics, ideology, culture, media and communication. In addition, in the field of scientific interest  of modern researchers was a regional-typological aspect. Of particular scientific interest is the study of national models of  informatization of society in terms of a deeper understanding of the dynamics of media development of countries. The choice  of the theoretical model, in the parameters of which the real characteristics of the modern information space of the countries of the Arabian Peninsula are inscribed, is based on a number of actual factors. The countries of the Arabian Peninsula  retain a complex intertwining of traditions and modernity, yesterday and today. At the same time, by a number of indicators  of economic development, by the end of the second millennium, some of the countries of the region have approached the  level of the most developed European states (Saudi Arabia), and other countries still remain in the last century (the Republic  of Yemen).
Keywords: mass media; communication; speech; communication policy; the countries of the Arabian Peninsula; public opinion